(untitled) (Innovative professional education, 2024)
For bachelors in the organization and technology of farming, the task of forming economic competence is important primarily because of the high social responsibility of future farmers. Their successful and effective professional activity is possible when personal values are combined with awareness of the need to form a new economic position. The relevance of the researched problem is determined by the need to develop new approaches to the development of students’ economic competence in conditions of intensive transformation of economic relations in all spheres of activity. The purpose of the study is to develop the economic competence of bachelors in the organization and technology of farming.